The Journey Through Rehabilitation: A Study of People with Acquired Brain Injury in Western Australia - O’Callaghan, Annalise Marie (Curtin University, 2017)
Acquired brain injury is a complex, individualised condition causing lifelong disability and affecting thousands of Australians and their families. Listening and learning from the perspectives of people with Acquired Brain Injuries and their families is essential to improving their experiences as they journey through rehabilitation. A qualitative study hearing the voices of people with ABI, their families and health professionals identified gaps in long-term service provision and the benefits of a 24/7 interprofessional rehabilitation model.